To simplify the expression \( 17 + (-32) \), you can think of it as subtracting 32 from 17.
So:
\[ 17 + (-32) = 17 - 32 \]
Calculating that gives:
\[ 17 - 32 = -15 \]
Therefore, the simplified expression is \(-15\).
The correct answer is: -15.
17 + (−32)=
Desmos Scientific Calculator
(1 point)
Responses
-15
-15
49
49
-49
-49
15
1 answer
To simplify the expression \( 17 + (-32) \), you can think of it as subtracting 32 from 17.
So:
\[ 17 + (-32) = 17 - 32 \]
Calculating that gives:
\[ 17 - 32 = -15 \]
Therefore, the simplified expression is \(-15\).
The correct answer is: -15.